THE IMPACT OF MINERAL FERTILIZATION AND ATMOSPHERIC PRECIPITATION ON YIELD OF FIELD CROPS ON FAMILY FARMS - Munćan, Mihajlo (Economics of Agriculture, 2016)
The feld crop production, as the most important branch of plant production of the Republic of Serbia, in the period 2002-2011, was carried out on an average of over 2.7 million hectares, 82.7% of which took place on the individual farms/family holdings. Hence, the subject of research in this paper covers yields of major feld crops realized on family farms in the region of Vojvodina in the period 1972-2011. The main objective of the research is to study the interdependence of utilization of mineral fertilizers and atmospheric precipitation during the vegetation period and realized yields of major feld crops on family farms in the observed period. The regression analysis was applied in order to verify dependencies and determine the form of dependence of achieved yields from examined variables. The results showed that the main limiting factors for obtaining high and stable yields of feld crops is inadequate use of fertilizers and the lack of precipitation during the vegetation period.